Local electrogram delay recorded from left ventricular lead at implant predicts response to cardiac resynchronization therapy: retrospective study with 1 year follow up - Polasek, Rostislav; Kucera, Pavel; Nedbal, Pavel; Roubicek, Tomas; Belza, Tomáš; Hanuliakova, Jana; Horak, David; Wichterle, Dan; Kautzner, Josef (BMC cardiovascular disorders, 2012)
BACKGROUND: Considerable proportion of patients does not respond to the cardiac resynchronization therapy (CRT). This study investigated clinical relevance of left ventricular electrode local electrogram delay from the beginning of QRS (QLV). We hypothesized that longer QLV indicating more optimal lead placement in the late activated regions is associated with the higher probability of positive CRT response. METHODS: We conducted a retrospective, single-centre analysis of 161 consecutive patients with heart failure and LBBB or nonspecific intraventricular conduction delay (IVCD) treated with CRT. We routinely intend to implant the LV lead in a region with long QLV. Clinical response to CRT, left ventricular (LV) reverse remodelling (i.e. decrease in LV end-systolic diameter - LVESD ≥10%) and reduction in plasma level of NT-proBNP >30% at 12-month post-implant were the study endpoints. We analyzed association between pre-implant variables and the study endpoints. RESULTS: Clinical CRT response rate reached 58%, 84% and 92% in the lowest (≤105 ms), middle (106-130 ms) and the highest (>130 ms) QLV tertile (p < 0.0001), respectively. Longer QRS duration (p = 0.002), smaller LVESD and a non-ischemic cardiomyopathy (both p = 0.02) were also univariately associated with positive clinical CRT response. In a multivariate analysis, QLV remained the strongest predictor of clinical CRT response (p < 0.00001), followed by LVESD (p = 0.01) and etiology of LV dysfunction (p = 0.04). Comparable predictive power of QLV for LV reverse remodelling and NT-proBNP response rates was observed. CONCLUSION: LV lead position assessed by duration of the QLV interval was found the strongest independent predictor of beneficial clinical response to CRT.
Keywords: Electrophysiologic Techniques, Cardiac; lineární modely; Chi-Square Distribution; srdeční blokáda; srdeční resynchronizační terapie; Humans; Heart Failure; srdeční selhání; lidé středního věku; funkce levé komory srdeční; Ventricular Remodeling; Multivariate Analysis; Predictive Value of Tests; natriuretický peptid typu B; Equipment Design; Female; rizikové faktory; Aged; dospělí; výsledek terapie; senioři; lidé; Biomarkers; Cardiac Resynchronization Therapy Devices; Cardiac Resynchronization Therapy; rozdělení chí kvadrát; časové faktory; Heart Block; Adult; Peptide Fragments; elektrofyziologické techniky kardiologické; biologické markery; ženské pohlaví; multivariační analýza; Male; Middle Aged; prediktivní hodnota testů; Retrospective Studies; Linear Models; Treatment Outcome; design vybavení; Czech Republic; blokáda Tawarova raménka; Aged, 80 and over; peptidové fragmenty; senioři nad 80 let; retrospektivní studie; Natriuretic Peptide, Brain; Bundle-Branch Block; Risk Assessment; Česká republika; prostředky srdeční resynchronizační terapie; mužské pohlaví; remodelace komor; Time Factors; hodnocení rizik; Ventricular Function, Left; Risk Factors